Present subjunctive embedded in focus-on-form activities: a case of formal instruction in the L2 Spanish classroom - Loza Ordonez, Victoria Ellen (Kansas State University, 2020)
A large corpus of research focused on the acquisition of the subjunctive in the Spanish classroom suggests that this mood possesses a deep inherent complexity. This is mainly the case due to two factors: a) the elaborated syntactic constructions prompted by the subjunctive, and b) the varied interpretations and meanings conveyed by this mood. As such, learners of Spanish as a foreign language (hereafter FL) undergo a lengthy process in order to comprehend, implement and naturally and efficiently employ the subjunctive in their speech at the written and spoken level. Having said that, raising the communicative value of the subjunctive may elevate its noticeability (Collentine, 2010). Activities that support focus-on-form are designed to attract a learner’s attention to a particular form, especially during communication (Ellis, 2016). Moreover, current research supports increased accuracy with pair work, especially when dealing with complex grammatical forms (Baleghizadeh, 2010). For that reason, activities involving collaborative tasks should be implemented into the classroom (Fernández Dobao, 2012). In an effort to equip language instructors with more efficient practices to facilitate and accelerate learners’ comprehension and development of the subjunctive, this study surveys 1) the impact of the design of the task (i.e. focus-on-form) and 2) two different working modes (i.e. individuals and pairs) embedded in the use of the present subjunctive. To this end, 33 participants completed a battery of activities consisting of an individual written activity with two different versions, and a collaborative oral and written assignment. Version A of the individual written activity was at the paragraph level, while version B only required participants to express ideas at the sentence level. Results suggest that the design of version B allowed them to perform better than that of version A. Additionally, working collaboratively seemed to have yielded communicative opportunities that led participants to produce a higher number of accurate sentences.
Keywords: Focus-on-form; Pair work; Communicative learning; Spanish mood; Intermediate Spanish